2018
DOI: 10.3855/jidc.9677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biofilm formation and efflux pumps in ESBL and carbapenemase producing Klebsiella pneumoniae

Abstract: Introduction: Klebsiella pneumoniae is an opportunistic pathogen that causes a range of diseases. The appearance of extended-spectrum β-lactamase -and carbapenemase-producing strains, in addition to the biofilm-forming phenotype, is a major problem in the clinical environment. Methodology: A total of 33 clinical K. pneumoniae isolates were used in this study. Antimicrobial susceptibilities were assessed by a disc diffusion assay. Biofilm formation was determined by a microtiter plate assay, staining with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…showed that 51% of collected K . pneumoniae were ESBL-producers, 49% of them were carbapenemase-producers [ 8 ]. These results may be attributed to the excessive use of these antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that 51% of collected K . pneumoniae were ESBL-producers, 49% of them were carbapenemase-producers [ 8 ]. These results may be attributed to the excessive use of these antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Japoni-Nejad et al showed that 12 isolates were carbapenemases-producers and 8 of them were AmpC-producers [34]. Besides, Yazgan et al showed that 51% of collected K. pneumoniae were ESBL-producers, 49% of them were carbapenemase-producers [8]. These results may be attributed to the excessive use of these antibiotics.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, resistance to tigecycline has emerged in multidrug-resistant (MDR) strains of various pathogens, in particular, Acinetobacter baumannii, Klebsiella pneumoniae and Enterobacteriaceae. In recent decades, various strains of tigecycline-resistant pathogenic bacteria have been reported from the USA, UK, France, Saudi Arabia, Greece, Spain, Germany and Taiwan [3,4]. Most of them changed from tigecyclinesensitive to tigecycline-resistant during treatment, with the highest reported minimum inhibitory concentration (MIC) of tigecycline being 24 µg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation is another crucial virulence mechanism of this organism responsible for its nosocomial importance. Biofilm is a group of microorganisms that are attached to living and non-living surface and plays a protective role against antibiotics and macrophages (Yazgan et al 2018). Ever since the first report of biofilm formation phenomenon in K. pneumoniae emerged in 1988, many research works have suggested a strong association between biofilm formation, virulence and multidrug resistance (MDR) mechanisms (Nirwati et al 2019).…”
Section: Introductionmentioning
confidence: 99%